The representation of Indonesian cultural diversity in middle school English textbooks - Parlindungan, Firman; Rifai, Irfan; Safriani, Afida (Universitas Pendidikan Indonesia, 2018)
In Indonesia, exposure to the English language is primarily mediated through the use of English textbooks. What cultural knowledge and whose culture are represented in these textbooks become a critical issue because culture interweaves both language and thought. With this in mind, this study aims to examine how Indonesian cultural diversity and whose cultures are represented in middle school English textbooks. We argue that diversity and multicultural perspectives represented in these textbooks are the core of English language learning and teaching. We also contend that language textbooks play a pivotal role in the acquisition of both linguistic and cultural knowledge of English. Drawing on Kress and Van Leeuwen’s (2006) semiotic approach to analyzing textual and non-textual representations of cultures, we found that the 2013 English textbooks for Grades 7 and 8 permeate Indonesian cultural values and practices that do not provide a balanced and equal depiction of Indonesian cultural diversity. The findings suggest the importance of inclusive representation of the richness of Indonesian local culture in a more salient manner, especially those of minority groups. Pedagogically, teachers are expected to design language materials with cultural sensitivity and appropriation for the inclusiveness of other cultural values that might not be covered in the textbooks.